PTH-111 Changes in Mri Enetrography in Crohn'S Patients Treated with Adalimumab. (4th June 2013) - Bajwa, A; Vijayan, S; Haynes, A; Hawker, P; Sinha, R
Abstract : Introduction: MRI enterography has become the gold standard radiological assessment for Crohn's disease. The radiological response of Crohn's disease following mono therapy with Adalimumab is not clearly documented. The aim of this study was to compare pre and post treatment MRI enterograms in Crohn's patients on treatment with Adlumimab monotherapy Methods: 24 consecutive Crohn's patients being treated with Adalimumab monotherapy according to NICE guidelines. Median age was 37.5years (range 21–66). Pre treatment MRI enterograms were compared with enterograms at a median of 6 months after commencement of treatment. MRI parameters compared were bowel thickness (BT), enhancement ration (ER), diffusion value (DV) and the apparent diffusion coefficient (ADC). Post treatment enterograms were compared with 24 control subjects without inflammatory bowel disease. Changes in these parameters were further correlated with changes in biochemistry (FBC, CRP and Albumin) Results: Significant improvements in all MRI parameters were noted with treatment (Mean changes: BT 2.0, p = < 0.001; ER –0.32, p = < 0.0001;DV –111.09, p = < 0.0001, ADC 0.18, p = < 0.0001). There was a trend to an improvement in biochemical parameters, none of which were statistically significant. Changes in biochemical parameters did not correlate with MRI changes. On comparison with control MRI enterograms, ER was the only parameter not significantly deleterious in Crohn's patients indicating ongoing inflammation Conclusion: Marked radiological improvement is apparent 6 months into Adalimumab monotherapy for Crohn's disease. However, significant features of inflammation persist indicating mucosal healing has not been achieved in this treatment period. Disclosure of Interest: None Declared.